Peningkatan Prasarana Desa Cenrana Baru Melalui Pengadaan Papan Wicara dan Penunjuk Arah - Ahmad Ismail; Andi Edli; Annisa Salsabila; Muhammad Rayhan Rifaldi; Syahruni Widyastuti R; Vergita Astrid Ana Maria Lakebo; Yusril Yusuf (Universitas Hasanuddin, 2023)
One of the important components that can support the development of tourist villages is the availability of adequate village facilities and infrastructure. Reviewing the potential of Cenrana Baru villages as a tourist village is still needed for reference to the specialized village infrastructure on availability of information and accessibility. Implementation of the Procurement of Workage and Points of the Cenrana Village in the Cenrana Baru Village is conducted in an effort to support the availability of tourist destination information and auxiliaries that can facilitate the reach of access to the Cenrana Baru village. The method of implementing this activity is preceded by observing at several strategic locations as a place of laying the speaker and direction boards. The process of manufacturing using wood base materials still considering the environmentally friendly and endurance elements. Through this program of activities is expected to better introduce the Cenrana Baru village and its potential to the wider community.